Climate finance and emission reductions: What do the last twenty years tell us? - Claire Gavard; Niklas Schoch (ZEW - Leibniz-Zentrum für Europäische Wirtschaftsforschung, 2021)
In the framework of the Paris Agreement implementation, financial transfers remain a major point of negotiation for addressing equity concerns raised by the ambitious climate objectives. In complement to the theoretical, experimental and numerical studies that have examined the role of transfers in facilitating coalitions, we conduct the first empirical analysis of their impact on national carbon emission reductions. We build on the existing literature to develop a conceptual framework which models continuous national emission choices in the presence of financial transfers. We infer an equation of the impact of mitigation and adaptation finance on national emissions of recipient countries. We test the derived hypothesis using carbon emissions data of non-OECD countries in the last 20 years. We find that public adaptation and mitigation finance tend to increase emissions. Private mitigation finance seems to reduce them only after five years following the transfers.
Keywords: C23; C70; D02; K33; Q54; Q58; 330; International environmental agreements; public goods; transfers; climate finance; emission reductions; adaptation; climate policy